Sosialisasi Digital Agrotourism dalam Upaya Peningkatan Kesejahteraan Petani Kopi Gombengsari, Banyuwangi - Dedi, Mohamad; Harlina, Tintin (TEKIBA : Jurnal Teknologi dan Pengabdian Masyarakat, 2022)
The coffee farming business in Gombengsari Village is an independent coffee plantation that has existed since the colonial era. Various business development programs have been carried out by private and government parties, but have never received training on Digital Agrotourism. The aspect of digital marketing knowledge and skills is a major obstacle in product marketing. Digital Agrotourism, is hoped that it will provide an increase in the skills of the coffee farming community of Gombengsari Village in marketing their products. The stages of the activity are carried out by initial identification of the education level of the farmers, followed by the preparation of a schedule for socialization and training implementation. The activity was supported by 2 students as part of the implementation of the “Merdeka Belajar Kampus Merdeka (MBKM)”. The results of the activity showed that more than 85% of the participants had increased knowledge and were able to open their digital stalls